Evaluating the Role of Pharmacists in Managing Antibiotic Use and Combating Multi-Drug Resistance in Hospital Settings - Ruchita S. Math; Jay B. Prajapati; Dhvanil J. Desai; Krishna J. Desai; Jalpesh B. Rathod (International Journal of Antibiotics, 2026)
Antibiotic resistance is now one of the crucial health issues of the world, especially in hospitals where high usage of antimicrobials is increasing the rate at which multi-drug resistant (MDR) organisms appear. Misprescription, extended treatment, and over-use of broad spectrum antibiotics play a large role in the development of resistance resulting in the growth of morbidity, mortality and health care expenditure. This review analyses the essentiality of pharmacists in controlling the use of antibiotics and preventing MDR with the help of antimicrobial stewardship programs (ASPs). Pharmacists can play a role in prescription review and optimization, dose change, therapeutic drug monitoring, de- escalation plan, intravenous-oral conversion, and adverse drug reaction surveillance. It has been shown that pharmacist-based interventions lead to a decrease in the use of inappropriate antibiotics, increase in clinical outcomes, hospital length of stay, health care spending, and the stabilization or reducing MDR rates. Even though challenges of implementation include resource constraints and policy gaps, institutional support can be strengthened by implementing advanced technologies and improving the effectiveness of stewardship. Owing to the above, pharmacist-led antimicrobial stewardship is a sustainable approach and cost- efficient in maintaining antibiotic efficacy and enhancing patient safety within hospitals.
Keywords: Clinical pharmacist; Healthcare outcome; Hospital settings; Rational antibiotic use; antibiotic resistance; antimicrobial stewardship; multidrug resistance